Wind over tide. Issue 542 (July 2014) - Mahony, John D.
Abstract : The article 'Reflections on the Woolwich Ferry' [1] brought back some childhood memories. I remember being whisked away with my siblings from the verdant pastures of north-west Kent by bus and tram to Woolwich for a ride on one of the 'Free Ferry' paddle steamers; there were four of them and their passing in the mid 1960s was not universally welcomed. It was indeed a real treat that consumed just a little more than a full working day. The depths of a winter school holiday could find us huddled, privileged below the ferry decks on a gantry near the fire hole to receive the welcoming hot blast as its doors opened to accommodate the hand-stoked coke. It was hand-stoked to reduce smoke output, and each steamer could make about eight knots. Presumably health and safety considerations now would not allow for such a luxury of positioning. However, it was not always wine and roses. To borrow a phrase from one of Kipling's poems, it was sometimes a case of 'not with this wind blowing, and this tide', for there were rare occasions when journeys were temporarily delayed by exceptionally windy weather. The elements below (river velocity effect) conspired with the elements above (wind velocity effect) to delay ferry movements. The earlier article proposed a velocity model to deal with effects due only to the river flow and it is the purpose of this note to extend that argument by considering also a velocity effect due to the wind, because the superstructure on a ferry can be as susceptible to the wind as is the keel to the tide.